Migratory sub-populations of afferent lymphatic dendritic cells differ in their interactions with Mycobacterium bovis Bacille Calmette Guerin. - Hope, J; Guzman, E; Cubillos-Zapata, C; Stephens, SA; Gilbert, S; Prentice, H; Sopp, P; Howard, C; Charleston, B (2012)
Understanding how pathogens or vaccine antigens are targeted to dendritic cell (DC) subsets is important for disease pathogenesis studies and vaccine design. We characterised the sub-populations of migrating bovine DC with functional and phenotypic diversity present in pseudoafferent lymph draining the skin. These skin draining DC exist as a series of maturation dependent subsets with differential capacities for antigen uptake and cytokine expression, and include both Langerhans' cells (LC) and dermal derived cells. Furthermore, Mycobacterium bovis Bacille Calmette Guerin, a vaccine which is administered by the intradermal route, was only taken up by a small number of the migrating DC, which were SIRPα(+) and expressed the mannose receptor and CD1b. This was evident following in vitro infection and also in vivo following inoculation of green fluorescent BCG over the lymphatic cannulation site. Only the SIRPα(+) DC were able to present antigen to T cells isolated from BCG vaccinated calves. Furthermore, presentation of BCG antigens by DC to T lymphocytes was ineffective compared to mycobacterial proteins. However, mycobacterial antigen 85 was delivered more effectively to DC via an adenoviral vector and the magnitude of the subsequent antigen-specific T cell response was significantly increased. This study further extends our understanding of the biology of migrating DC, identifies potential explanations for the modest success of BCG vaccination and demonstrates that targeted delivery of antigens via adenoviruses to DC can improve antigen presentation.